How Perceived Usefulness And Perceived Ease Of Use Affecting Intent To Repurchase? - Keni Keni (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
This study was commencedin order to determine whether or not perceived usefulness and perceived ease of use positively affecting consumers’ intention to repurchase, both in a direct and indirect manner through both trust and customer satisfaction. A sumof 250 respondents joined this study,whilea total of 236 data were deemed usable to be further processed and analyzed in this study. Survey method was applied in this study, in which all of the data gathered from the respondents using questionnaires which were distributed both personally and electronically. All of the data then were analyzed using PLS-SEM method. In accordance with the results, author conclude that both perceived usefulness and perceived ease of use play a significant and important role in affecting consumers’ intention to repurchase, both directly and indirectly toward customer satisfaction and trust, in which trust plays a stronger role as a mediator as compared to satisfaction.